Creating animal models by genetic techniques - Gomas, Emmanuel (Henry Stewart Talks, 2015)
Choosing the right animal models, Inserting a transgene into an organism model (random or targeted integration), Controlling space and time of transgene expression, Genome editing via CRISPR-Cas9, Examples of genetically engineered models, Latest developments in genetic engineering